A Two Dimensional Facial Features Analysis for Gender-based Comparison Using Morphometrics Approach - Agbolade, Olalekan; Shahrel Ahmad, Azree; ., . (International Journal of Engineering and Technology, 2018)
Making a gender comparison between male and female is not a difficult task for human beings but the science of gender comparison of faces by humans is completely unfathomable due to commonality of gender comparison in both humans and other animal species. Significant gender differences between masculine and feminine exist in many facial regions such as eyes, nose, mouth, cheek and chin; which have not been critically looked into. This research characterizes and analyzes the gender comparison in the human face as a function of face features and identifies the features which contribute significantly to the uniqueness of the face using morphometrics techniques such as Principal Component Analysis (PCA), Thin-Plate Spline (TPS) Warping and Procrustes Superimposition (PS). The results demonstrate that the male face is significantly different from that of female based on the analysis of the selected facial features which provides the basis for gender-based comparison of faces. Â